1996
DOI: 10.1002/clc.4960190408
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with frequent premature ventricular complexes and nonsustained ventricular tachycardia after coronary artery bypass graft surgery

Abstract: Background: Previous studies in small groups of predominantly nongeriatic patients showed that complè ventricular arrhythmias occurring after coronary artery graft (CABG) surgery are of no prognostic significance. The purpose of this study was to compare the prognosis of patients with and without advanced grade ventricular arrhythmias (AGVA) after CABG in a large group of patients. [In this paper, AGVA is used as an abridged definition of frequent premature ventricular complexes (PVCs) and nonsustained ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…VT carries a high mortality risk, both during the acute phase and after hospital discharge [6][7][8][9][10]. On the other hand, nonsustained ventricular tachycardia does not seem to represent an ominous sign for the postoperative prognosis of surgically revascularized patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…VT carries a high mortality risk, both during the acute phase and after hospital discharge [6][7][8][9][10]. On the other hand, nonsustained ventricular tachycardia does not seem to represent an ominous sign for the postoperative prognosis of surgically revascularized patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, frequent PVCs (>30 per hour) may reduce ventricular function and therefore have an adverse impact on the short-term outcome. There was no significant difference in mortality in patients with versus patients without frequent postoperative PVCs and NSVT (8 versus 5%), at an average follow-up of 3 years, in a study including 185 postoperative patients [137]. However, in another study of 126 patients with postoperative PVCs, it was shown that patients with left ventricular ejection fraction (LVEF) of <40% had a 75% mortality rate and 33% incidence of sudden death at an average followup of 15 months, whereas none of the patients with preserved left ventricular function had sudden death [135].…”
Section: Prognosismentioning
confidence: 84%
“…On the other hand, frequent PVCs (>30 per hour) may have an impact on short-term outcome by reducing ventricular function. A study [138] of 185 patients reported no significant differences in mortality rates at an average followup of 3 years in patients with versus patients without frequent postoperative PVCs and nonsustained ventricular tachycardia (NSVT) (8% versus 5%). However, another study [139] of 126 patients with postoperative complex ventricular ectopies showed that patients with impaired left ventricular ejection fraction (<40%) had a 75% mortality rate and 33% incidence of sudden death at an average followup of 15 months, whereas none of the patients with preserved left ventricular function had sudden death.…”
Section: Ventricular Tachyarrhythmiasmentioning
confidence: 99%
“…Among patients who survive in-hospital sustained ventricular arrhythmias, up to 40% have a recurrence. As many as 20% of these patients die from cardiac causes within 24 months [137, 138]. …”
Section: Ventricular Tachyarrhythmiasmentioning
confidence: 99%